Knowledge and Institutions (Knowledge and Space,, 2018)
This open access book bridges the disciplinary boundaries within the social sciences to explore the role of social institutions in shaping geographical contexts, and in creating new knowledge. It includes theorizations as well as original empirical case studies on the emergence, maintenance and change of institutions as well as on their constraining and enabling effects on innovation, entrepreneurship, art and cultural heritage, often at regional scales across Europe and North America. Rooted in the disciplines of management and organization studies, sociology, geography, political science, and economics the contributors all take comprehensive approaches to carve out the specific contextuality of institutions as well as their impact on societal outcomes. Not only does this book offer detailed insights into current debates in institutional theory, it also provides background for scholars, students, and professionals at the intersection between regional development, policy-making, and regulation.